Praise as Classroom Communicative Reinforcing Device: Perceptions of Vietnamese University Students - L. T.T. Do; A. T.L. Vu (Высшее образование в России)
One of the biggest challenges for teachers is to foster a positive learning environment in which students become motivated and engaged in classroom activities. Growing concerns have been shown about how evaluative praise functioned as a good reinforcer for students' achievement and desirable behaviour affects students' motivation to learn, depending on teachers' messages communicated with students. This study examined the impacts of different types of teacher praise upon university students' perceptions. Case study was employed to collect the data through observations and semi-structured interviews. The results highlighted that students perceived differently towards kinds of praise that they earned. They tended to respond to specific, verbal praise in a more positive way because of its explicit recognition and precise information about their contributions, hence it could make better their self-concept as well as help them keep motivated. Also, high-achievers sought for ability praise whereas low-achievers desired to draw effort praise from teachers. Educators would benefit these findings for the pedagogical purposes.